2018
DOI: 10.18203/2320-1770.ijrcog20180191
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status and its determinants in subpopulation of pregnant women in rural Central India

Abstract: Background: There is an increased demand for iodine and thyroid hormones, in pregnancy starting from the early weeks of pregnancy suggesting that there may be a need for additional supplements of iodine in high risk population to prevent iodine deficiency and its associated disorders. Hence this study was undertaken to determine the iodine status and its determinants in a subpopulation of pregnant women from a rural area of Central India.Methods: A hospital based, cross-sectional, observational study was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The recommended dietary intake of iodine during pregnancy and the cut-off values for UIE concentration were revised by the Technical Consultation convened by WHO Secretariat in 2007 and were later endorsed by WHO/ICCIDD/UNICEF. 16,17 The standards of salt iodization in India require an iodine content of 30ppm at the time of manufacture, so as to deliver 15ppm at the retail level (due to loss during transportation). The iodine content of the packaged salt was tested from household women at random in our study and found consistent with package description.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended dietary intake of iodine during pregnancy and the cut-off values for UIE concentration were revised by the Technical Consultation convened by WHO Secretariat in 2007 and were later endorsed by WHO/ICCIDD/UNICEF. 16,17 The standards of salt iodization in India require an iodine content of 30ppm at the time of manufacture, so as to deliver 15ppm at the retail level (due to loss during transportation). The iodine content of the packaged salt was tested from household women at random in our study and found consistent with package description.…”
Section: Discussionmentioning
confidence: 99%
“…Two cross-sectional studies from Rajasthan, revealed median UIC was 127µg/L and 118µg/L in pregnant women of >28 weeks of gestation which indicates deficiency. 6 Another study conducted in New Delhi 19 and Haryana 20 showed median urinary iodine 150µg/L indicating dietary sufficiency. The study in Dhaka 21 showed that maternal urinary iodine is negatively correlated with their serum TSH.…”
Section: Urinary Iodine In Second Trimester Of Pregnancy: a Cross Secmentioning
confidence: 98%
“…4 As far as India is concerned heavy rainfall/flooding results in mineral depletion and makes the soil iodine deficient. 6 Dietary iodine deficiency leads to altered synthesis of thyroid hormone and/or thyroid enlargement (goiter).…”
Section: Introductionmentioning
confidence: 99%